A novel integrated approach for path following and directional stability control of road vehicles after a tire blow-out. (1st September 2017) - Wang, Fei; Chen, Hong; Guo, Konghui; Cao, Dongpu
Highlights: A novel linearized decoupling control procedure is proposed. For a class of second order multi-input-multi-output non-affine system. The closed-loop system is robustly stable. The evaluating indicators for controller performance are put forward. Abstract: The path following and directional stability are two crucial problems when a road vehicle experiences a tire blow-out or sudden tire failure. Considering the requirement of rapid road vehicle motion control during a tire blow-out, this article proposes a novel linearized decoupling control procedure with three design steps for a class of second order multi-input-multi-output non-affine system. The evaluating indicators for controller performance are presented and a performance related control parameter distribution map is obtained based on the stochastic algorithm which is an innovation for non-blind parameter adjustment in engineering implementation. The analysis on the robustness of the proposed integrated controller is also performed. The simulation studies for a range of driving conditions are conducted, to demonstrate the effectiveness of the proposed controller.